PHYTOCHEMICAL SCREENING AND ANTIOXIDANT PROFILING OF Averrhoa bilimbi and Diplazium esculentum: A COMPARATIVE IN-VITRO APPROACH - Khadija Begum; AKM Saifuddin (Journal of Global Pharma Technology, 2026)
Free radical–induced cell damage contributes to many diseases, which can be prevented using natural antioxidants like Averrhoa bilimbi leaf and Diplazium esculentum, both traditionally recognized for their antioxidant properties. This study aimed to screen and quantifies phytochemicals, assess in vitro antioxidant properties, and compare the antioxidant activities of these studied plants. Plant samples from various areas of Chattogram were collected and extracted with 80% methanol. Secondary metabolites were qualitatively and quantitatively analyzed, and antioxidant efficacy was evaluated through different in vitro assays to compare the efficacy of both plants. Among the secondary metabolites, tannin was absent in A. bilimbi leaf extract, while saponin was undetected in D. esculentum extract. D. esculentum exhibited higher phenolic (18.58 mg GAE/100 g DE) and flavonoid (61.48 mg RE/g DE) contents than A. bilimbi (11.85 mg GAE/100 g DE; 39.49 mg RE/g DE), indicating stronger antioxidant potential. Antioxidant activity, assessed via DPPH, FRAP, and H₂O₂ assays, showed that D. esculentum had greater DPPH scavenging (IC₅₀ = 29.07 mg/ml) and Fe³⁺ reducing power, while A. bilimbi exhibited better H₂O₂ scavenging (IC₅₀ = 8.32 mg/ml vs. 13.27 mg/ml for D. esculentum). This result could provide a meaningful insight about the D. esculentum that has potential as antioxidant than A. bilimbi leaf and can be applied in the development of new medicines. Keywords: Phytochemicals, A. bilimbi leaf, D. esculentum, In vitro approach, Antioxidant, Comparative study.